EVALUASI SISTEM PENYUSUNAN APBD DINAS PENDIDIKAN DAN KEBUDAYAAN PROVINSI KALIMANTAN BARAT - B51109007, RENDY NOVRIANSYAN (Jurnal KIAFE, 2013)
Title of The Research is evaluation of system budgeting Office of Education and Culture of West Kalimantan Province. Research background is as a Regional Working Units (RWU), Department of Education and Culture has a right to propose minimal budget of twenty percent (20%) of the total regional budget and liabilities as a device regional for carrying out the budgeting as well to do realization of conduct imposition of the budget. Research problems that raised is an indication that provinces have not fulfilled one of the main points of the special rules of legislation. The research objective was to determine the factors that impede the fulfillment of specific rules in the Regulation of the Minister of Home Affairs Number 22 Year 2011 on Guidelines for Preparation of Regional Budget for Fiscal Year 2012. Form of research is a case study and data collection techniques by observation, interview and documentary study of literature. Data processing techniques use descriptive analysis, analysis of organizational structure, flow chart and evaluate the results of the interview. The results of the research, is not fulfilled of the specific rules of the Minister of Home Affairs Regulation No. 22 of 2011 on Guidelines for Preparation of Budget for Fiscal Year 2012. Pengambat factor is the limited income, lack of infrastructure building of education, and lack of fund special alocation to province Keywords: Education, Budget, Budget